Prognostic analysis and mechanistic exploration of the autophagy-related exosome genes ITGA3, ITGB4, and PTK6 in pancreatic ductal adenocarcinoma - Liang, Lunbing; Guo, Pengcheng; Xiao, Mingming; Zu, Fuqiang; Hao, Guoliang; Zhang, Chaochun; Liu, Qingfeng (Discover. Oncology, 2025)
Pancreatic cancer (PC) is a highly malignant tumor with an extremely poor prognosis, but early diagnosis and treatment can significantly improve prognosis. This study aimed to screen autophagy-related exosome genes associated with poor prognosis in PC and to explore the underlying mechanisms in malignant progression via bioinformatics analysis to provide a reference for the diagnosis, treatment and prognosis evaluation of PC, especially pancreatic ductal adenocarcinoma (PDAC). Matrix files of 178 PC tissues (including 143 PDAC) and 167 healthy human pancreatic tissues and clinical data were downloaded from the UCSC Xena database, exosome database (exoRbase) and autophagy database (HADb), and the relevant mechanisms were explored by bioinformatics methods, including differential analysis, LASSO regression analysis, survival analysis, functional analysis, immune infiltration analysis and drug sensitivity analysis. Finally, the expression of related genes in PDAC was verified via immunohistochemistry. Our research results indicate that the autophagy-related exosome genes PTK6, ITGA3 and ITGB4 are independent risk factors for PC and may promote PC development and invasion by promoting cell–cell adhesion and cell–matrix adhesion, inhibiting tumor cell autophagy, promoting nerve infiltration, reducing CD8 + T-cell content, and increasing M0 and M2 macrophage content. Drug susceptibility analysis showed that crizotinib, tamoxifen, ixazomib, and carboplatin had inhibitory effects on ITGA3, ITGB4, and PTK6.